Assessing the risk of residues of the toxin indospicine in bovine muscle and liver from north-west Australia. (May 2019) - Netzel, Gabriele; Palmer, Dieter G.; Masters, Anne M.; Tai, Samantha Y.; Allen, Jeremy G.; Fletcher, Mary T.
Abstract: Indospicine is a natural toxin occurring only in Indigofera plant species, including the Australian native species I. linnaei . These perennial legumes are resistant to drought and palatable to grazing livestock including cattle. Indospicine accumulates in the tissues (including muscle) of animals grazing Indigofera and these residues persist for several months after exposure. Dogs are particularly sensitive to indospicine with reports in past decades of hepatotoxicosis and mortalities in dogs after dietary exposure to indospicine-contaminated horse and camel meat. The risk for human consumption is not known, and the current study was undertaken to assess indospicine levels in cattle going to slaughter from divergent regions of Western Australia, and to predict the likelihood of significant residues being present. Muscle and corresponding liver samples from 776 cattle originating from the Kimberley and Pilbara Regions in the tropical north of the state, where I. linnaei is prevalent, and 640 cattle from the South West and South Coast Regions in the temperate south west of the state, where the plant is not known to occur, were collected at abattoirs over four seasons in 2015–2017. Indospicine levels were measured by LC-MS/MS and ranged from below detection to 3.63 mg/kg. No indospicine residues were detected in any of the animals originating from the South West and South Coast Regions. Prevalence of indospicine residues in cattle from the Kimberley Region was as high as 33% in spring and 91% in autumn, with positive animals being present in most consignments and on most properties. The average prevalence of indospicine residues from the Kimberley and Pilbara Regions throughout the survey period was 63%. @Risk best fit probability distributions showed ninety-fifth percentile (P95) indospicine concentrations of 0.54 mg/kg for muscle and 0.77 mg/kg for liver in cattle originating from the Kimberley and Pilbara Regions during the survey period. When considered with average Australian meat consumption data, the estimated consumer exposure from this P95 muscle was 0.32 μg indospicine/kg bw/day, which compared favourably with our calculated provisional tolerable daily intake (PTDI) of 1.3 μg indospicine/kg bw/day. However canine exposure is of potential concern, with active working dog exposure calculated to exceed this PTDI by a factor of 25, based on a P95 indospicine concentration of 0.54 mg/kg in muscle. Highlights: The hepatotoxin indospicine accumulates in tissues of animals grazing Indigofera. Indospicine detected in meat of cattle from Indigofera regions collected at abattoir. @Risk modelling employed to determine risk to human and canine consumers. Measured indospicine levels were higher in autumn than in spring abattoir collections.